Prioritizing user preferences for quasi - Public space by using analytic hierarchy process (AHP): bursa Podyum park, Turkey case - Ersoz, Nazli Deniz; Demir, Sara; Gokkaya, Merve Dilman; Aksoy, Onur (Emerald Group Publishing Ltd, 2024)
PurposeThis study aims to fill the lack of quantitative studies of user preferences in quasi-public spaces to observe the use of quasi-public spaces by questioning the contemporary needs of urban communities and to develop design strategies accordingly.Design/methodology/approachWithin the scope of this study, public space design elements affecting users' preferences in the quasi-public spaces of the Podium Park shopping center in Bursa, Turkey were evaluated. By considering the spatial characteristics of the study area, 4 main and 15 subcriteria were determined and utilized by analytic hierarchy process (AHP). These criteria were evaluated by experts and locals with a participatory approach.FindingsAccording to the obtained results, events (S2), sun/shade (C2), safety (P3) and planting (U4) subcriteria were determined as the vital elements for quasi-public spaces.Originality/valueAlthough the concept of quasi-public space has been discussed for nearly 30 years, it has been observed that there are no quantitative studies to determine the criteria of user preferences in these open spaces in the literature. This study is the first quantitative research for user preferences in quasi-public spaces and there is no previous study on this subject and study area in Turkey.
Keywords: Quasi-public space; Quantifying user preferences; Multi-criteria decision making (MCDM); Analytic hierarchy process (AHP); Podyum park